FROM SHIFTS TO SELF-CARE: EXAMINING WORK-LIFE QUALITY AMONG NURSES IN MOH HOSPITALS - Al-Dosari, Khalid Mohammed (Research Journal of Health, Medicine and Nursing, 2024)
Nurses are the backbone of the healthcare system, providing diverse and essential services to promote health and deliver quality care. Their roles have evolved beyond institutional care, encompassing a wide range of disciplines within healthcare organizations. Despite their significant contributions, nurses often remain an overlooked and undervalued workforce in the healthcare industry. This invisibility is concerning, especially in the face of today's complex healthcare landscape, where nurses encounter various challenges. These challenges include manpower shortages, long working hours, workplace hazards, and the immense pressure of their roles. Moreover, the healthcare environment can be fraught with violence, which directly impacts care settings and services. One key aspect that influences the wellbeing of nurses and their performance is the quality of life (QOL). Quality of Life is a subjective evaluation of one's life based on cultural, societal, and personal values, encompassing their goals, expectations, standards, and concerns. It is intricately linked to their work environment and their relationships within it. The concept of Quality Work Life (QWL) has gained prominence as a critical issue. Many studies have explored this topic across various settings, emphasizing the need to enhance the quality of work-life for nurses. This paper delves into the challenges and opportunities for improving the QWL of nurses in the healthcare sector